Pengaruh Model Pembelajaran Berbasis Masalah dengan Metode Eksperimen pada Materi Cahaya Terhadap Hasil Belajar Fisika Siswa Kelas VIII SMPN 2 Gunungsari Tahun Ajaran 2014/2015 - Ardian Firmansyah; Kosim Kosim; Syahrial Ayub (Department of Physics Education, Universitas Mataram, 2015)
The purpose of this study was to determine the effect of problem based learning model with experiment method of the topic light on studentÃ¢â¬â¢s physics learning outcomes of SMPN 2 Gunungsari academic year 2014/2015. The design of this study used experimental research with pretest-posttest control group design. The population of this study is students of grade VIII SMPN 2 Gunungsari, with sampling was using cluster random sampling technique. The samples are the students of class VIII A as experimental class and class VIII B as control class. Data results studying by test used is polled variance t-test. The results of the analysis of hypothesis test obtained tcount= 2,71 compared with ttable = 2,.02 at the significance level of 5%. According to criteria of hypothesis testing, if tcount > ttable, then Ho is rejected and Ha accepted. It can be concluded that there are effect of problem based learning model with experiment method of the topic light on studentÃ¢â¬â¢s physics learning outcomes of SMPN 2 Gunungsari academic year 2014/2015.